Tongxinluo enhances the effect of atorvastatin on the treatment of atherosclerosis with chronic obstructive pulmonary disease by maintaining the pulmonary microvascular barrier. Issue 1 (13th October 2022) - Kuang, Xiangnan; Wang, Yafen; Liu, Shiqiao; Chang, Liping; Yin, Yujie; Li, Zhen; Liu, Yi; Li, Wenyan; Hou, Yunlong; Wang, Hongtao; Liang, Junqing; Jia, Zhenhua
Abstract: Atherosclerosis (AS) is a common comorbidity of chronic obstructive pulmonary disease (COPD), and systemic inflammation is an important mechanism of COPD with AS. Tongxinluo (TXL) improves the function of vascular endothelial cells. We aimed to prove that impairment of pulmonary microvascular barrier function is involved in COPD‐mediated aggravation of AS and investigate whether TXL enhances the effect of Ato (atorvastatin) on COPD with AS by protecting pulmonary microvascular endothelial barrier function. In vivo, a COPD with atherosclerotic apolipoprotein E knockout (AS ApoE −/− ) mouse model was established by cigarette smoke combined with a high‐fat diet. The animals were administered TXL, Ato, and TXL + Ato once a day for 20 weeks. Lung function, lung microvascular permeability, lung inflammation, systemic inflammation, serum lipid levels, atheromatous plaque formation, and endothelial damage biomarkers were measured. In vitro, human pulmonary microvascular endothelial cells (HPMECs) were pretreated with TXL and incubated with cigarette smoke extract to establish the model. The permeability of the endothelial monolayer, inflammatory cytokines, endothelial damage biomarkers, and tight junction (Tj) proteins were determined. Cigarette smoking significantly exacerbated the high‐fat diet‐induced pulmonary function decline, pulmonary microvascular endothelial barrier dysfunction, inflammation, and atherosclerotic plaques. These changes were reversed by TXL–Ato; the combination was more effective than Ato alone. Furthermore, TXL protected the HPMEC barrier and inhibited inflammation in HPMECs. COPD aggravates AS, possibly through the destruction of pulmonary microvascular barrier function; thus, lung inflammation triggers systemic inflammation. In treating COPD with AS, TXL enhances the antiatherosclerotic effect of Ato, protecting the pulmonary microvascular barrier. Abstract : COPD aggravates AS, possibly through the destruction of pulmonary microvascular barrier function; thus, lung inflammation triggers systemic inflammation. In treating COPD with AS, TXL enhances the antiatherosclerotic effect of Ato, protecting the pulmonary microvascular barrier.